2021
DOI: 10.33552/abeb.2021.06.000634
|View full text |Cite
|
Sign up to set email alerts
|

"Study of Effects a New Resuspending Solution Which Was Nanotechnologically Upgraded on Lipoperoxidation, Catalase Activity and Red Blood Cell Peroxidation Resistance in Donor Blood Components"

Abstract: This work is licensed under Creative Commons Attribution 4.0 License ABEB.MS.ID.000634.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Considering that due to the activation of glycolysis Micromag-B significantly increases the amount of macroergic compound (ATP) [41,42], as well as the formation of the reduced form of the coenzyme nicotinamideadenindinucleotide phosphate (NADPH2) with the transition of oxidized form of glutathione to reduced [43], conditions for starting enzymatic methylation processes are created. The latter most likely complements the mechanism of action of magnetite nanoparticles (Micromage-B).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that due to the activation of glycolysis Micromag-B significantly increases the amount of macroergic compound (ATP) [41,42], as well as the formation of the reduced form of the coenzyme nicotinamideadenindinucleotide phosphate (NADPH2) with the transition of oxidized form of glutathione to reduced [43], conditions for starting enzymatic methylation processes are created. The latter most likely complements the mechanism of action of magnetite nanoparticles (Micromage-B).…”
Section: Resultsmentioning
confidence: 99%
“…By the example of studying human erythrocytes, it was shown that magnetite nanoparticles (NPs) reliably change the polarization structure of the water sector of the cell microenvironment and, consequently, regulate the permeability of erythrocyte membranes (Belousov, 2013(Belousov, , 2014Belousov et al, 2018Belousov et al, , 2019. Resuspension of physiological saline solution treated with magnetite nanoparticles (ICNB) significantly reduces the level of primary and secondary products of lipid peroxidation and inhibits the Schiff reaction of neutral lipid peroxidation during the storage stages of preserved donor erythrocytes (Belousov et al, 2021).…”
Section: Introductionmentioning
confidence: 99%